Mewujudkan Kesadaran Energi Melalui Konsep Khalifah Fi al-’Ard - Muhammad Iqbal (Jurnal Penelitian, 2016)
This paper describes the concept of khalifah fil’ardi as representatives of God in conserving nature. This study aims to instill awareness of energy derived from natural resources. This type of research is the research library (Library Research) and this research is a qualitative descriptive study. Based on the analysis and the data that I researched, the author concludes that a comprehensive knowledge about energy awareness is the basis of the khalifah fil’ardi. Realizing energy awareness in society becomes the latest concept of khalifah fil’ardi.